Harnessing Fishers’ Knowledge for Sustainable Fishery on Lake Victoria: The case of Wakiso District Kigungu Fishing ground Uganda - Zula Namubiru; George Openjujru Ladaah; Josje Van Der Linden; Kellen Aganyira (Adult Education Research Conference, 2022)
This study will explore fishers’ ways of learning through participatory action research; fostering lifelong learning and reflections informally/ non-formally enabling participation in the conservation of the fishery resource contrary to the top-down approach.
Keywords: Fisher; illegal fishing; learning